Preoperative Urine Analysis is An Effective Tool to Predict Fever After Miniaturized Percutaneous Nephrolithotomy on Large Renal Stones - Lu, Ze-Hong; Lin, Tsung Yen; Huang, Ho Shiang; Liu, Chan Jung (Urology Journal, 2021)
Purpose: To investigate the preoperative and intraoperative potential risk factors associated with miniaturized percutaneous nephrolithotomy (mPCNL) fever in the treatment of patients with large renal stones. Materials and Methods: All patients with renal stones larger than 2.5 cm, who had undergone mPCNL, were included in the period between April 2018 and September 2019. Logistic regression analyses were performed to identify clinical variables associated with post-operative fever (>38°C). Results: A total of 53 patients were enrolled for whom the median maximal stone length was 3.08 cm. 24 (45%) patients had a fever after mPCNL. Significantly more patients with urine WBC ≥ 27(/HPF) had a fever after surgery (p = 0.004). No significant between-group differences in urine cultures were found for the fever and non-fever groups (p = 0.094). Stepwise and multivariable logistic regression analyses all revealed that urine WBC ≥ 27(/HPF) is the only risk factor for developing post-mPCNL fever. Based on the highest body temperature, all of the patients were assigned into no fever, mild fever (37.5 ≤ Temp < 38.0), and fever groups, and an ordinal logistic regression analysis still supported the premise that the result of urine analysis is strongly associated with post-mPCNL fever. Conclusion: Large renal stones are challenging to treat and associated with severe complications. Approximately 45% of large renal stone patients treated via mPCNL developed a fever. Urine WBC can easily and directly predict the risk of fever.